Increasing Commitment To The Profession Through Organizational Climate, Personality, And Job Satisfaction Of Private Higher Lecturers In The City Of South Tangerang - N. Lilis Suryani; Aida Vitalaya Syafri Hubeis; Widodo Sunaryo (CV. Inara, 2021)
This study aims to find an effort to increase Commitment to the Profession through Organizational Climate, Personality, and Job Satisfaction. The population in this study is permanent lecturers who have the position of functional lecturer at 5 private universities in South Tangerang City with a total of 379 lecturers. The sampling technique used proportional random sampling with the Slovin formula with an error margin of 5% with a total sample of 195 lecturers. The data analysis method used in this research is Path Analysis. This study concludes 1) There is a direct influence of organizational climate on a commitment to the profession. 2) There is a direct influence of personality on a commitment to the profession. 3) There is a direct effect of job satisfaction on a commitment to the profession. 4) There is a direct influence of organizational climate on job satisfaction. 5) There is a direct influence of personality on job satisfaction. 6) There is an indirect influence of organizational climate with a commitment to the profession through job satisfaction. 7) There is an indirect influence of personality with a commitment to the profession through job satisfaction.